2015
DOI: 10.18632/oncotarget.2928
|View full text |Cite
|
Sign up to set email alerts
|

Increase of miR-199a-5p by protoporphyrin IX, a photocatalyzer, directly inhibits E2F3, sensitizing mesenchymal tumor cells to anti-cancer agents

Abstract: Hepatocellular carcinoma (HCC) is a leading cause of cancer-related deaths. Protoporphyrin IX (PPIX) has been used for photodynamic therapy. Mesenchymal cancer cells adapt to tumor microenvironments for growth and metastasis possibly in association with miRNA dysregulation. In view of the effect of PPIX on cancer-related genes, and its potential to inhibit tumor growth and migration/invasion, this study investigated whether PPIX enables mesenchymal liver tumor to restore dysregulated miRNAs, and if so, whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Recently, miR-199a-5p has been reported to exhibit inhibitory effects on autophagy (27). For instance, Lee et al observed that protoporphyrin IX, a photocatalyzer, could increase the expression of miR-199a-5p, which further inhibited E2F transcription factor 3 and sensitized mesenchymal tumor cells to chemotherapy drugs (28). In the present study, it was observed that miR-199a-5p inhibited DDP-induced autophagy.…”
Section: Mir-199a-5p Negatively Mediates the Protein Expression Of Besupporting
confidence: 58%
“…Recently, miR-199a-5p has been reported to exhibit inhibitory effects on autophagy (27). For instance, Lee et al observed that protoporphyrin IX, a photocatalyzer, could increase the expression of miR-199a-5p, which further inhibited E2F transcription factor 3 and sensitized mesenchymal tumor cells to chemotherapy drugs (28). In the present study, it was observed that miR-199a-5p inhibited DDP-induced autophagy.…”
Section: Mir-199a-5p Negatively Mediates the Protein Expression Of Besupporting
confidence: 58%
“…It is well known that miRNAs function via regulating their target protein by binding to the 3’ untranslated regions (UTRs) of target messenger RNAs (mRNAs), resulting in mRNA degradation or the blockade of mRNA translation . Previously, miR‐199a‐5p was reported to functions as a tumor suppressor by targeting connective tissue growth factor (CTGF), integrin β1, hypoxia‐inducible factor 1 alpha (HIF‐1α), E‐cadherin, hexokinase 2, frizzled class receptor 6 (FZD6), E2F transcription factor 3 (E2F3), Wnt family member 2 (WNT2) and cyclin‐dependent kinase inhibitor 1C (P57, CDKN1C) …”
Section: Discussionmentioning
confidence: 99%
“…In present study, we showed that miR-199a-5p, frequently down- 19,20 Previously, miR-199a-5p was reported to functions as a tumor suppressor by targeting connective tissue growth factor (CTGF), integrin β1, hypoxia-inducible factor 1 alpha (HIF-1α), E-cadherin, hexokinase 2, frizzled class receptor 6 (FZD6), E2F transcription factor 3 (E2F3), Wnt family member 2 (WNT2) and cyclin-dependent kinase inhibitor 1C (P57, CDKN1C). [21][22][23][24][25][26][27][28][29] Clathrin is considered the prototype vesicle coat protein whose self-assembly mediates sorting of membrane cargo and recruitment of lipid modifiers. 30 In the past decades, most of studies were focused on clathrin mediated endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…In HCC, miR-199a-5p levels were down-regulated accompanied by E2F3 overexpression. After PPIX treatment, miR-199a-5p was modulated to increase and led to the inhibition of E2F3 expression [ 53 ]. In murine models of colon cancer, miR-143 and miR-145 played tumor suppressive functions by targeting Cdk6, CCND2 and E2F3 [ 54 ].…”
Section: Mirna-e2f3 Interactive Relation: Mirnas Regulate E2f3mentioning
confidence: 99%